Legal Consequences Of An Abandoned Land: Agrarian Justice Against Rights Of Property - Saputra, Rahma Dwi Maulana; Rahmatiar, Yuniar; Abbas, Muhammad (Journal of Law and Policy Transformation, 2025)
Land ownership and utilization in Indonesia has important dimensions both economically, socially, and politically, and is expressly regulated in the Basic Agrarian Law of 1960 and Article 33 paragraph (3) of the 1945 Constitution which emphasizes the social function of land. However, in practice, there is still a lot of land that is abandoned, causing social inequality, injustice, and obstacles to development. This research aims to analyze the implementation of Government Regulation Number 20 of 2021 concerning the Management of Abandoned Areas and Land as well as the legal consequences for rights holders who do not use their land. The research method is a normative juridical approach with descriptive analysis, based on a literature study of laws and regulations and related literature. The results of the study show that the implementation of PP 20/2021 in regulating unused land, that land that is deliberately left vacant or not used according to its intended purpose can be designated as abandoned land and has legal implications as explained in articles 3, 6, 7, and 30, both for individual rights holders and legal entities, except in certain conditions that are indeed excluded by regulations. The legal consequence of land abandonment is the abolition of land rights for the sake of law and the transition of its status into state land that can be used for public purposes, agrarian reform, and national development programs as explained in articles 30, 31, and 32. Therefore, this regulation not only emphasizes the aspect of legal certainty, but also acts as a strategic means to realize agrarian justice, equity, and maximum land use for the welfare of the community.